Effect of the activation atmosphere on the activity of Fe catalysts supported on SBA-15 in the Fischer–Tropsch Synthesis - Cano, Leonardo Andres (2011)
An iron catalyst supported on SBA-15 was prepared and activated in H2 stream and in synthesis gas (H2:CO = 2:1) stream, in order to be used in the Fischer–Tropsch Synthesis. The different activation treatments led to different Fe species in fresh catalysts: a-Fe, Fe3O4 and Fe2+ diffused into the SBA-15 walls in H2-Fe/SBA-15 and v-Fe5C2, Fe3O4 and Fe2+ in H2:CO–Fe/SBA-15. These initial differences in the ‘‘bulk’’ structure of the solids disappear when both catalysts are ‘‘working’’. However, a higher production of total hydrocarbons, higher CO conversion and more CH4 and light gases were obtained for H2-Fe/SBA- 15 over 6 days. Besides, a higher selectivity toward light olefins was obtained with H2 Fe/SBA-15 during the first 24 h on reaction stream, but this selectivity decreases with the reaction time. These results are explained considering that the iron carbides produced from a-Fe are more active and/or have smaller sizes than that obtained from a-Fe2O3.